ANALISIS PERAN GURU DALAM MEMBANGUN KARAKTER SISWA MELALUI IMPLEMENTASI KURIKULUM MERDEKA DI UPTD SMPN 1 TORGAMBA - Harahap, Siti Amroh; Julyanti, Eva; Harahap, Amin (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2025)
The role of teachers in implementing the Independent Curriculum at UPTD SMPN 1 TORGAMBA is the subject of this research. This research involves teachers and students as subjects, with a quantitative approach and uses observation, interviews and documentation for data collection. Research findings show that the role of teachers is very vital in forming students' character through the implementation of the Independent Curriculum which emphasizes religious values, morals, diversity, as well as critical thinking skills, collaboration and independence. The research results also show that SMPN 1 TORGAMBA has succeeded in implementing the Independent Curriculum in various ways, such as conducting cognitive diagnostic assessments, creating teaching modules, implementing learning, and designing projects to improve student profiles. However, the lack of offline training causes a number of challenges, especially related to teachers' understanding of the Merdeka Curriculum.